Capacity of the 45 and Up Study to mobilise evidence-based improvements in cancer control: lung cancer case study - Marianne F Weber; Preston J Ngo; Emily Banks; Julia Steinberg; David E Goldsbury; Paul Grogan; Karen Canfell (Sax Institute, 2022)
Objective: Over the 15 years since the 45 and Up Study (the Study) was established, researchers have harnessed its capacity for enabling rigorous, comprehensive investigation of cancer causes, care, and outcomes. For the first time in Australia, the entire cancer-control continuum could be investigated by linking questionnaire data with cancer registry notifications, hospital records, outpatient medical services and prescription medications at scale. Here, we use lung cancer as a case study to demonstrate the Study's potential to improve cancer control. Method: Narrative description. Results: Between 2006-2013, approximately 1200 participants in the Study cohort who had no prior history of cancer were diagnosed with lung cancer, allowing the generation of novel, policy- and practice-relevant evidence for tobacco control, screening, and systems of care. The Study produced evidence on the continuing impact of smoking, including that 'light smoking' (1-5 cigarettes/day) is associated with nine times the risk of lung cancer compared to never-smoking; and that 54% of lung cancers could be avoided long-term if all Australians who smoked were to quit. The Study was used to validate a lung cancer screening risk prediction tool, correctly identifying 70% of the participants with a history of smoking who developed lung cancer within a 6-year period as 'high-risk'. Potential inequities in lung cancer care were identified using the Study cohort, including suboptimal levels of radiotherapy utilisation, below benchmark levels of systemic therapy for patients with metastatic disease, and high numbers of emergency department presentations prior to diagnosis. Participants with lung cancer reported poorer quality of life than those with almost any other cancer type, and about 50% reported severe physical functioning limitations. The Study also provided the infrastructure for the first comprehensive report on lung cancer health system costs. Lessons learnt: As a statewide, population-based cohort, the Study provides reliable estimates of cancer risk, health services utilisation, and person-centred outcomes that can inform policy and practice decision making; and has provided the backbone for localising policy-relevant insights from international experience. We have found that the direct involvement of clinicians and policy makers in research design, and engagement with community networks, can yield tractable, policy-relevant, and ultimately impactful scientific insights.